PENGEMBANGAN E-MODUL BIOLOGI APLIKATIF-INTEGRATIF BERBASIS PEMBELAJARAN BERDIFERENSIASI UNTUK MATERI VIRUS DI SMA - Asmayani; Seprida, Riski; Rosmiati, Etti (Universitas Cokroaminoto Palopo, 2025)
This study aims to develop an applicative-integrative E-Module (Electronic Module) based on differentiated learning as a form of support for the implementation of the Independent Curriculum in Senior High Schools. This study uses a Research and Development (R&D) approach by adapting the 4D development model developed by Thiagarajan, Semmel, and Semmel. This model consists of four main stages, namely Define, Design, Develop, and Disseminate. Thus, it can be concluded that the RPP for the Virus material is included in the